Design of a hybrid solar photovoltaic system for Gollis University’s administrative block, Somaliland - S. Adam, Jama; A. Fashina, Adebayo (International Journal of Physical Research, 2019)
This work presents the design of a 100kVA hybrid solar power system for Gollis University’s administrative block, Hargeisa, Somaliland. Prior to the system design, a preliminary field work on the site was performed to essentially measure the power/energy consumption of Gollis university’s administrative block. The results from the site survey was then used to select the appropriate equipment and instrument required for the design. This was achieved by calculating the energy consumption and then sizing the solar panel, battery, inverter and charge controller. The battery back-up time analysis at full load was also carried out to determine the effectiveness of the inverter size chosen. The inverter system was modeled and simulated using the MATLAB/Simulink software package. The simulation was used to study the reliability of the size of inverter chosen for the design, since the failure of most photovoltaic systems is ascribed to inverter failures. The results from the MATLAB/Simulink simulation showed that the inverter selected for the hybrid PV system has the ability to maximize the power produced from the PV array, and to generate sinusoidal AC voltage with minimum output distortion. The results also revealed that the PV solar system can provide a back-up time of 47.47 hours. The implications of the results are then discussed before presenting the recommendations for future works.